Morphological and Molecular Characterization of Trichotylenchus dispersus (Nematoda: Dolichodoridae), a Newly Recorded Plant-Parasitic Nematode in the Rhizosphere Soil of Tomato Plants in Thailand - Sroisai, Pornthip; Beesa, Natthidech; Jindapunnapat, Kansiree (Trends in Sciences, 2024)
Trichotylenchus sp. is a migratory ectoparasitic nematode (PPN) that causes hypoplasia disease symptoms in economic plants, such as maize and banana. In this study, soil samples were collected from 6 locations in a tomato field in Khon Kaen Province, Thailand, for the purpose of nematode extraction using the Cobb’s sieving and flotation-centrifugation techniques. Morphological and molecular characterization of the collected PPN identified it as Trichotylenchus sp., a PPN not previously found in Thai tomato fields. Morphologically, the nematode has a C-shaped body, a rounded lip region, robust stylet and dorsal gland orifice located 2.0 ± 0.5 µm from the base of basal knobs. The tail is conically shaped, and the cuticle exhibits annulations with 3 incisures in the lateral field. The morphological characteristics observed closely matched Trichotylenchus sp. To confirm the identity, diagnosis was done using Polymerase Chain Reaction (PCR) molecular technique. Nematode DNA amplification was conducted with different target genes using primer sets AB28/TW81 for ITS1-5.8S-ITS2 and D2A/D3B for D2-D3 region of the 28S rRNA. The PCR amplification showed DNA fragments of approximately 950 and 800 bp, respectively. The sequences obtained were compared with those in the NCBI GenBank, which showed a 98.0 - 99.4 % identity match with Trichotylenchus dispersus specimens previously documented in China. In addition, the phylogenetic trees reiterated a nematode grouping with T. dispersus, 100 % bootstrap value. To the best of our knowledge, this is the first report of the presence of T. dispersus in the soils of tomato field in Thailand. This nematode is likely to become a major factor limiting tomato production yields if not properly managed. HIGHLIGHTS Six plant-parasitic nematodes (PPNs) were found to be associated with the tomato gown in field. A newly recorded PPN in the genus, Trichotylenchus, found in Thailand, has been documented in this study. Morphological and molecular characterization identified PPN as Trichotylenchus disperses. This is the first report on incidence of dispersus in a tomato field in Thailand. GRAPHICAL ABSTRACT